Mathematical evaluation of context transfer and multicast fast reroute in multicast enabled network mobility management - Mohd Aman, Azana Hafizah; Hassan Abdalla Hashim, Aisha; Mohd. Ramli, Huda Adibah (Science & Engineering Research Support soCiety, 2017)
Internet applications such as web based monitoring; live internet video, online video, video conference, webcam viewing and internet video to TV are highly used in today’s IP communication. The trends of these applications are, that they are played on mobile devices and distributed to many end users. Multicast communication over IP contributes to the end users applications distribution. It has been discovered by a CISCO research that mobile multicast traffic will soon reach zetabyte in 2019. The aim of this paper is to introduce new method that enable multicast in network mobility management. The new method is using context transfer and multicast fast reroute technique. The proposed method is quantitatively evaluated in terms of packet loss and service recovery time